Role of RIM101 for Sporulation at Alkaline pH in Ashbya gossypii - Wasserstrom, Lisa (J Fungi (Basel), 2021)
Microorganisms need to sense and adapt to fluctuations in the environmental pH. In fungal species, this response is mediated by the conserved pacC/RIM101 pathway. In Aspergillus nidulans, PacC activates alkaline-expressed genes and represses acid-controlled genes in response to alkaline pH and has important functions in regulating growth and conidia formation. In Saccharomyces cerevisiae, the PacC homolog Rim101 is required for adaptation to extracellular pH and to regulate transcription of IME1, the Initiator of MEiosis. S. cerevisiae rim101 mutants are defective in sporulation. In Ashbya gossypii, a filamentous fungus belonging to the family of Saccharomycetaceae, little is known about the role of pH in regulating growth and sporulation. Here, we deleted the AgRIM101 homolog (AFR190C). Our analyses show that Rim101 is important for growth and essential for sporulation at alkaline pH in A. gossypii. Acidic liquid sporulation media were alkalinized by sporulating strains, while the high pH of alkaline media (starting pH = 8.6) was reduced to a pH ~ 7.5 by these strains. However, Agrim101 mutants were unable to sporulate in alkaline media and failed to reduce the initial high pH, while they were capable of sporulation in acidic liquid media in which they increased the pH like the wild type.